Tuesday

October 21, 2014

October 21, 2014

Posted by **WINSTON** on Monday, March 10, 2014 at 11:20pm.

can some one explain the problem and answer to me step by step please.. I missing the process

- math -
**Steve**, Monday, March 10, 2014 at 11:39pmx(6x+1) < 15

6x^2 + x - 15 < 0

now you have a parabola. You need to find where it crosses the x-axis, and between those two points, it will lie below the x-axis.

(2x-3)(3x+5) < 0

so, the roots are at x = -5/3 and 3/2

Between those two values, the parabola lies below the x-axis.

As a check, let's try the original conditions.

x(6x+1) < 15

at x = -5/3, x(6x+1) = 15

at x = 3/2, x(6x+1) = 15

Now check something in between, say x = -1,0,1

f(x) = 5,0,7 all < 15.

How about a few outside -5/3 < x < 3/2 ?

f(-2) = 22 > 15

f(2) = 26 > 15

Take a look here:

http://www.wolframalpha.com/input/?i=x%286x%2B1%29+%3C+15

- math -
**herp_derp**, Monday, March 10, 2014 at 11:42pmInitial Problem

x(6x + 1) < 15

Simplify left side.

6x^2 + x < 15

Move 15 to left side.

6x^2 + x - 15 < 0

Factor.

(2x - 3)(3x + 5) < 0

Now, x MUST be BETWEEN the LESSER value and the GREATER value. (it is between because this is a "LESS THAN" inequality)

-5/3 < x < 3/2

**Answer this Question**

**Related Questions**

Algebra help - f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is...

MATH - calculate missing dimension. a) cylinder has volume 1m3 and height of 0....

english! - Make sure you understand the topic(s) is a step in the research ...

8 grade math - Can somebody please help me I don't understand this problem.? ...

Quick math help - In which step below does a mistake first appear in simplifying...

6 grade math - Can you help me with my new math homework? Regroup each mixed ...

Math - How would you explain how to do this problem step by step in words? The ...

Math - evaluate the expression ₆ P ₀ I am not sure how to do this ...

Math - 2(5x + 1) = 3(3x + 7) a) x = 19 b) x = 20 c) x = 21 Can you please ...

Calculus - 1/a+1 + 1/a-1 I solved this out by multiplying the (a+1) by (a-1) and...